2007
DOI: 10.1021/jm0703183
|View full text |Cite
|
Sign up to set email alerts
|

Structure−Activity Relationships of Phenyl-Furanyl-Rhodanines as Inhibitors of RNA Polymerase with Antibacterial Activity on Biofilms

Abstract: The dramatic rise of antibiotic-resistant bacteria over the past two decades has stressed the need for completely novel classes of antibacterial agents. Accordingly, recent advances in the study of prokaryotic transcription open new opportunities for such molecules. This paper reports the structure-activity relationships of a series of phenyl-furanyl-rhodanines (PFRs) as antibacterial inhibitors of RNA polymerase (RNAP). The molecules have been evaluated for their ability to inhibit transcription and affect gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
64
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 74 publications
(67 citation statements)
references
References 36 publications
0
64
1
Order By: Relevance
“…Compound 1 also lacked activity against Staphylococcus aureus and Bacillus subtilis (Table 4). We have no obvious explanation for the discrepancy between our data for compound 1 and the previously published results (15), especially since the structure of compound 1 (Table 1) was confirmed by full spectroscopic analysis (see the supplemental material) to be the same as that previously examined (15). In contrast to the results for compound 1, we confirmed that the other two furanyl-rhodanines (compounds 2 and 3) reported to possess antibacterial activity (4, 16) did indeed prevent the growth of S. aureus, B. subtilis, and E. coli (Table 4).…”
contrasting
confidence: 99%
See 4 more Smart Citations
“…Compound 1 also lacked activity against Staphylococcus aureus and Bacillus subtilis (Table 4). We have no obvious explanation for the discrepancy between our data for compound 1 and the previously published results (15), especially since the structure of compound 1 (Table 1) was confirmed by full spectroscopic analysis (see the supplemental material) to be the same as that previously examined (15). In contrast to the results for compound 1, we confirmed that the other two furanyl-rhodanines (compounds 2 and 3) reported to possess antibacterial activity (4, 16) did indeed prevent the growth of S. aureus, B. subtilis, and E. coli (Table 4).…”
contrasting
confidence: 99%
“…However, it is underexploited, since the rifamycins are the only RNAP inhibitors that have been developed for clinical use (2,8,14). Recently several furanyl-rhodanines that apparently possess antibacterial activity and inhibit Escherichia coli (RNAP) were described (15). This series had been expanded from a compound considered to be a specific RNAP inhibitor on the basis of cross-screening against unrelated enzymes and failure to inhibit in an in vitro transcription-translation assay using a reticulocyte lysate (15).…”
mentioning
confidence: 99%
See 3 more Smart Citations